2008
DOI: 10.1093/jmt/45.3.307
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Music as a Mnemonic Device on Recognition Memory for People with Multiple Sclerosis

Abstract: Research shows that people with multiple sclerosis exhibit learning and memory difficulties and that music can be used successfully as a mnemonic device to aid in learning and memory. However, there is currently no research investigating the effectiveness of music mnemonics as a compensatory learning strategy for people with multiple sclerosis. Participants with clinically definitive multiple sclerosis (N = 38) were given a verbal learning and memory test. Results from a recognition memory task were analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…MT interventions include singing, playing instruments, improvisation, making music, music listening, rhythmic entrainment, rhythmic auditory stimulation (RAS), song choice, sharing meaningful songs, musical autobiographies, musical life review, music mnemonics, recording music, musical identity, movement to music, and overall engagement with music. [32][33][34][35][36][37][38][39][40][41][42][43] Approaches have included Nordoff Robbins, neurologic MT (neuro-MT), psychodynamic MT, and cognitive behavioral therapy. 8,33,37,39,40,44,45 The goals of MT may include improving emotional status (adjustment to illness, mood states, expression of emotions), and enhancing neurologic performance (gait, Therapeutic use of the Arts for Patients with MS speech, cognitive function), thereby facilitating activities of daily living and improving quality of life.…”
Section: Music Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…MT interventions include singing, playing instruments, improvisation, making music, music listening, rhythmic entrainment, rhythmic auditory stimulation (RAS), song choice, sharing meaningful songs, musical autobiographies, musical life review, music mnemonics, recording music, musical identity, movement to music, and overall engagement with music. [32][33][34][35][36][37][38][39][40][41][42][43] Approaches have included Nordoff Robbins, neurologic MT (neuro-MT), psychodynamic MT, and cognitive behavioral therapy. 8,33,37,39,40,44,45 The goals of MT may include improving emotional status (adjustment to illness, mood states, expression of emotions), and enhancing neurologic performance (gait, Therapeutic use of the Arts for Patients with MS speech, cognitive function), thereby facilitating activities of daily living and improving quality of life.…”
Section: Music Therapymentioning
confidence: 99%
“…47 Moore et al compared learning via speech with learning through music on a recognition memory task, and their findings suggest that music mnemonics may help less impaired patients. 34 One case study reported on a woman with MS in her thirties who used song-writing to gain insight and delve into her personal problems. 49 When she first started participating in MT she exhibited a self-defeating mindset, but after engaging in 10 MT sessions she was able to express her feelings and engage in self-disclosure, performed and recorded her song, and …”
Section: Conklyn Et Al Compared a 2-week Home-based Walking Program mentioning
confidence: 99%
See 1 more Smart Citation
“…Since interwoven with these are characteristics of successful mnemonics, music can be an appropriate mnemonic application. Moore et al (2008) characteristics, it becomes a powerful stimulus. The ease of attending to and acquiring structural characteristics within the material to be remembered, its intrinsic organizational characteristics, and use as a means to cue recall are all present conditions within music, making it a good learning facilitator, thus a good mnemonic strategy.…”
Section: Music As An Aid To Learningmentioning
confidence: 99%
“…Its efficacy has been described in subjects with traumatic brain injury, stroke and MS (Särkämö et al, 2008;Forsblom et al, 2009;Thaut et al, 2009). A study on passive music therapy reported that listening to music facilitates learning and memory in mildly impaired MS subjects (Moore et al, 2008).…”
Section: Introductionmentioning
confidence: 99%